On the von Neumann entropy of a bath linearly coupled to a driven quantum system - Erik Aurell; Ralf Eichhorn (New Journal of Physics, 2015)
The change of the von Neumann entropy of a set of harmonic oscillators initially in thermal equilibrium and interacting linearly with an externally driven quantum system is computed by adapting the Feynman–Vernon influence functional formalism. This quantum entropy production has the form of the expectation value of three functionals of the forward and backward paths describing the system history in the Feynman–Vernon theory. In the classical limit of Kramers–Langevin dynamics (Caldeira–Leggett model) these functionals combine to three terms, where the first is the entropy production functional of stochastic thermodynamics, the classical work done by the system on the environment in units of k _B T, and the second and the third other functionals which have no analogue in stochastic thermodynamics.